Inflation and risky investments - Hannu Laurila; Jukka Ilomäki (Journal of Risk and Financial Management, 2020)
The paper uses a Walrasian two-period financial market model with informed and uninformed constant absolute risk averse (CARA) rational investors and noise traders. The investors allocate their initial wealth between risky assets and risk-free fiat money. The analysis concentrates on the effects of decreasing value of money, or inflation, on the rational investors' behavior and the asset market. The main findings are the following: Inflation does not affect the informed investors' prediction coefficient but makes that of the uninformed investors diminish. Inflation does not affect rational investors' risk but makes the asset price more sensitive to fundament-based and sentiment-based shocks. Inflation changes the market price of the risky asset rise; while it has no effects on the informed investors' demand of the risky asset, it does affect the uninformed investors' demand. Finally, inflation makes the asset market more volatile.
Keywords: 330; Constant Absolute Risk Averse (CARA) utility function; information; negative interest rates; volatility